Diagnosing axial spondyloarthritis: estimation of the disease probability in patients with a priori different likelihoods of the diagnosis. (8th March 2021) - Poddubnyy, Denis; Proft, Fabian; Spiller, Laura; Protopopov, Mikhail; Rios Rodriguez, Valeria; Muche, Burkhard; Rademacher, Judith; Torgutalp, Murat; Vahldiek, Janis Lucas; Sieper, Joachim; Redeker, Imke
Abstract: Objective: To evaluate the diagnostic value of SpA parameters and their combination for the diagnosis of axial SpA in patients with an a priori different probability of the diagnosis. Methods: A total of 361 patients with chronic back pain and suspicion of axial SpA (181 referred by primary care physicians or orthopaedists, 180 recruited via an online screening tool) received a structured rheumatologic examination, which resulted into a diagnosis or exclusion of axial SpA. The prevalence of axial SpA indicating the pre-test probability was 40% in the physician-referred subgroup and 20% in the online screening subgroup. Sensitivities, specificities and likelihood ratios for SpA features were determined in both subgroups and the respective post-test probabilities of axial SpA were calculated. Results: The relative diagnostic value of single SpA features varied substantially between the groups with different referral pathways. For instance, HLA-B27 positivity increased the probability of the presence of axial SpA by 35% to 55% in online-screened patients and by 22% to 62% in physician-referred patients. The absence of HLA-B27 resulted in a sharp decrease in the probability of the presence of axial SpA in physician-referred patients (from 40% to 6%). This decrease was less sharp in the online screening group (from 20% to 10%). These differences were especially relevant in patients with a small number (one to two) of positive SpA features. Conclusion: The diagnostic value of SpA features varies in different patient populations, which should be considered in the diagnostic approach.